INFORMASI AKUNTANSI DAN NON AKUNTANSI PADA FENOMENA UNDERPRICING YANG TERJADI SAAT PENAWARAN UMUM SAHAM PERDANA PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Kurniawan, Lydia (Jurnal Akuntansi, 2014)
Abstract: In order to expand their business in several ways, for example companies can offer their shares to the general public. Underpricing is a phenomenon that often appears and is experienced by companies that conduct an Initial Public Offering on the various stock exchanges in the world, where the IPO price is set lower than the true value of the company. Underpriced shares often occur because of information asymmetry or inequality of information that occurs in the group of investors who have information and a group of investors who do not have the information about the prospects of the issuer company. This study examined whether the age of the firm, firm size, and return on assets (ROA) affect the level of IPO underpricing on the company at the Indonesian Stock Exchange. This study was measured by Initial Return underpricing. The objects in this study are 32 companies that did the initial public offering in 2002 to 2004 at the Indonesia Stock Exchange and experienced under pricing . Conclusions from the study indicate that the companies age and their size variables are not shown to affect the dependent variable Underpricing, while the variable Return on Assets (ROA) Under pricing are shown to affect the dependent variable at a significant level of 5%.